Predictive power of the HEMPA risk assessment method for musculoskeletal disorders in nurses and caregivers: insights and implications - Sayed Vahid Esmaeili; Ali Alboghobeish; Neda Izadi; Fatemeh Azizi; Fatemeh Dorfeshan; Ali Salehi Sahlabadi (BMC Nursing)
Abstract Introduction Work-related musculoskeletal disorders (WMSDs) pose a critical occupational health challenge for nurses and caregivers, with high prevalence rates impacting workforce sustainability and care quality. This study evaluates the predictive power of the HEMPA (Herramienta de Evaluación de Movilización de Pacientes) risk assessment method for WMSDs in these high-risk populations, addressing the urgent need for validated tools to guide ergonomic interventions. Methods This descriptive and analytical study involved 90 caregivers and nurses from various wards of a medical center in 2024. Data were collected through a three-part form supervised by researchers (demographics, body map musculoskeletal questionnaire, HEMPA tool). Logistic regression assessed HEMPA’s predictive capacity for WMSDs prevalence and its relationship with variables like age, gender, body mass index (BMI), and job characteristics. The predictive power of the HEMPA method for different body parts was evaluated using the area under the receiver operating characteristic (ROC) curve values. The study data were analyzed using Stata v.14 software, with a significance level of less than 5% for all tests (P  < 0.05). Result In this study, 90 caregivers and nurses participated with an age range of 24–60 years and BMI of 27.15 ± 4.02 kg/m2. Most of the participants (52.2%) were male, married (83.3%), and had a high school diploma (81.1%). The risk assessment of 16 different departments of the hospital was at the medium level. The highest prevalence of musculoskeletal disorders was reported in the lower back (93.3%) and neck (87.7%), while the highest intensity of pain was reported in the lower back (34.4%) and back (24.4%). The odds of suffering from musculoskeletal disorders were 0.47 times higher in the Left-Thigh (95% CI: 0.29–0.76) and Right-Thigh (95% CI: 0.29–0.76) areas compared to other body parts. Based on the ROC Curve values, the highest AUC values were for Left-Thigh (AUC = 0.79, 95% CI = 0.69–0.89) and Right-Knee (AUC = 0.76, 95% CI = 0.62–0.90), while the lowest AUC values were for Left-Ankle (AUC = 0.68, 95% CI = 0.57–0.79) and Right-Hand (AUC = 0.66, 95% CI = 0.55–0.78). Conclusion HEMPA effectively identifies WMSD risks, particularly in high-burden areas like the lower back and neck. This validation underscores HEMPA’s utility as a preventive tool, aligning with global efforts to reduce ergonomic hazards for caregivers and nurses. Furthermore, integrating HEMPA with digital monitoring platforms such as injury reporting software and wearable sensors for real-time risk assessment is proposed as a practical solution. Clinical trial number Not applicable.